The success pregnancy rate with estrous synchronization hormones in Madura cow - Muchamad Luthfi; Jauhari Efendy (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
This study aimed to determine the efficiency and effectiveness of the use of PGF2α and ovsynch (PGF2α and GnRH) estrous synchronization hormones on their ability to have an impact in the form of estrous and pregnancy symptoms in Madura cow. The material used were 182 Madura cows, was consisted by three treatments, namely A treatment with 62 cows; first day (H-0) was injected with PGF2α dose of 2 ml; 11th day (H-11) injected with the same hormone and dosage; then 3-4 days after the second AI (Artificial Insemination) injection directly; treatment B of 60 cows; first day (H-0) injected PGF2α dose 3 ml; 11th day (H-11) is injected again with the same hormone and dosage; then 3-4 days after injection of the second hormone directly AI; C treatments were 60 cows; given ovsynch treatment; that is, on the first day (H-0) injected with a 2.5 ml dose of the GnRH hormone; 8th day (H-8) injected with PGF2α dose 2 ml; the 10th day was injected again with the second GnRH hormone (2.5 ml dose), then the 11th day was directly AI. Sampling was done by purposive sampling method, which was choosing a cow that has a body condition score (BCS) between 5-7, normal reproductive organs and not in a state of pregnancy. The study design used a completely randomized design; Data were analyzed using the Kruskal Wallis test. The results showed that the administration of synchronous hormones to the percentage of estrous and pregnancy rate in all treatments showed no significantly different results (P > 0.05). The average percentage of estrous Madura cows in all treatments was 94.50%, while the average pregnancy rate was 68.66%, the highest yield in treatment C was 73.33%; followed by treatments A and B respectively 70.97% and 61.67%.